Legumes in the U.S. Virgin Islands - Oakes, A.J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Native, naturalized, and introduced legumes contribute significantly to the rangeland agriculture of the Virgin Islands. The plants most commonly used by livestock as grazing include species of Acacia, Aeschynomene, Cassia, Clitoria, Crotalaria, Desmodium, Galactia, Indigofera, Leucaena, Rhynchosia, and Teramnus. The main legumes cut for fodder include species of Acacia, Albizia, Cassia, Delonix, Erythrina, Leucaena, Samanea, and Tamarindus. Legumes generally increase livestock acceptance when browsed or mixed with forage grasses.